Serum gastrin levels in patients with colorectal cancer - Ahmet UYGUN; Can UYGURER; Namık K. NAZAROĞLU; Cengiz KAYHAN; Ergun SARAÇOĞLU; Celalettin ÇETİN and Necmettin KARAEREN (Turkish Journal of Gastroenterology, 2019)
-